Five new tribes in the Scrophulariaceae / K. Barringer - Barringer, Kerry (2007)
Four new tribes of Scrophulariaceae are described: Alonsoeae, Bowkerieae, Caprarieae, and Freylineae. The Globulariaceae are given new status as a tribe in the Scrophulariaceae.
Keywords: Scrophulariaceae